Phototherapy of extragenital white spot disease - B. A. Volnukhin; L. F. Znamenskaya; I. A. Kappusheva; N. L. Muradyan; A. S. Dvornikov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Objective. To study the effectiveness of UVA1therapy and PUVA therapy in patients with extragenital lichen sclerosus. Materials and methods. Effectiveness of the phototherapy methods was studied in 12 patients with extragenital lichen sclerosus (8 women, 4 men) aged from 19 to 61 years old with the disease history of 1-25 years. 6 patients received UVA1therapy while 3 patients received general PUVA therapy and 3 patients - local PUVA therapy. All the patients underwent phototherapy in the form of monotherapy. Results. After the treatment clinical improvement was observed in 6 patients from the UVA1 group (100%) and 4 patients from the PUVA group (66.7%), significant improvement of clinical picture and clinical remission were registered in 1 (16.7%) and 2 (33.3%) patients from the PUVA group, respectively. Phototherapy caused partial or full regress of main lichen sclerosus symptoms: sclerosis, induration, erythema, epidermal atrophy and skin hypopigmentation. The tolerability of treatment was satisfying, serious adverse effects were not reported. Conclusion. Conducted research indicates the effectiveness of UVA1therapy and PUVA therapy in patients with extragenital lichen sclerosus. Phototherapy may be a choice in the management of the disease.